Perancangan Jaringan Distribusi Sepatu yang Efisien dengan Pendekatan Center of Gravity dan Saving Matrix - Susiati, Devi; Nurmawati, Nurmawati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. MEC is a shoe company in Mojokerto, East Java. This company markets its products throughout Indonesia. To meet the demand for these products promptly, a new central distribution warehouse location was required. It is intended that companies can compete and survive with imported products and other local brand products. Products that reach the hands of consumers at the right time will win the market. This study aims to determine the location of warehouses that are efficient and effective in product marketing channels and minimize transportation costs by using the center of gravity and saving matrix methods. The processed data is primary data that focuses on 13 marketing area cities, especially on the island of Java. The calculation results are obtained using the center of gravity method, the new warehouse is located in Bantul, Yogyakarta with coordinate points (- 7.977838; 110.367226) and more optimal transportation costs of 47%. Furthermore, the data is processed using the saving matrix method, the distribution route is divided into 6 with a total distance traveled of 687.19 km.